PENGARUH UKURAN PERUSAHAAN, KOMITE AUDIT DAN AUDIT TENURE TERHADAP AUDIT DELAY DENGAN REPUTASI KAP SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Periode 2014-2016) - Yurisa Ratnasari; M Rasuli; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to determine the effect of firm size, audit committee and audit tenure to the acceptance of audit delay with public accounting firm’s reputation as a moderate. The samples of this research are mining companies which listed on the Indonesia Stock Exchange (BEI) in 2014 to 2016. The population of this research are 38 companies. Based on purposive sampling method, the total of final samples are 114 samples. Analysis of data is carried out using multiple regression method with the aid of SPPS version 17 computer program. The result of this research before moderating show that firm size and audit tenure are significant influence on audit delaywith significance level of 0,001 and 0,005.While audit committee has no effect on audit delaywith significance level of0,315. Public accounting firm’s reputation proved to moderate the effect of firm size on audit delay with significance level of 0,003. While Public accounting firm’s reputation do not give contribution to affect audit committee and audit tenure to minimize audit delay, with signification levels of 0.369 and 0.295.keywords : audit delay, firm size, audit committee, audit tenure, public accounting firm’s reputation